(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
The article examines modern approaches to biomechanical control in physical education and sports, based on the use of advanced technologies, including video analysis, electromyography, inertial sensors, and artificial intelligence. The refinement of methodological foundations for biomechanical control not only enhances the effectiveness of the training process through a detailed analysis of kinematic and dynamic parameters of motor activity but also contributes to reducing sports injuries by identifying critical loads, optimizing technical movement components, and providing personalized correction of individual biomechanical characteristics. The relevance of implementing these technologies for improving the efficiency of the training process, optimizing athletes’ technical preparation, and reducing injury risks has been established. A scientific analysis of the application of video analysis systems (Dartfish, Kinovea, Vicon Motion Systems), force platforms (Kistler, AMTI, Bertec), and electromyographic complexes (Delsys, Noraxon, BTS Bioengineering) has been conducted, allowing for the precise assessment of movement mechanics, load distribution, and muscle activity levels during physical exercises. Special attention is given to the prospects of using inertial sensors (Xsens, Moticon, STT Systems) for contactless analysis of motor activity in field research conditions. The role of artificial intelligence in sports biomechanics is examined, particularly the potential applications of OpenPose, AI Motion Analysis, and Google DeepMind for automated movement technique analysis. These tools have been shown to contribute to the personalization of training programs, the correction of technical errors in real time, and the overall improvement of physical performance. The study aims to identify the most effective methods for applying video analysis, electromyography, inertial sensors, and artificial intelligence in sports biomechanics. The use of modern technologies in biomechanical control significantly enhances the quality of the training process, improves athletic performance, and reduces injury incidence. The further evolution and comprehensive integration of these methods create prerequisites for an in-depth scientific analysis of the biomechanical aspects of motor activity, contribute to the development of high-tech control and performance prediction algorithms, and ensure scientifically grounded optimization of training programs, taking into account individual morphofunctional and adaptive characteristics. The obtained results will contribute to the advancement of scientific and methodological approaches to the use of biomechanical control in sports and physical education. Future research prospects are associated with the integration of multisensory platforms, the development of adaptive rehabilitation technologies, and the creation of automated systems for monitoring motor characteristics.